1990
DOI: 10.1104/pp.94.1.278
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Oxygen Emission and Uptake in Leaves by Pulsed, Time Resolved Photoacoustics

Abstract: Pulsed, time resolved photoacoustics has sufficient sensitivity to determine oxygen emission and uptake by single tumover flashes to leaves. The advantage over previous methodologies is that when combined with single turnover flashes the kinetics of the thermal and the gas signals can be resolved to 0.1 millisecond and separated. The S-state oscillations of oxygen formation are readily observed. The gas signal from common spongy leaves such as spinach (Spinacia sp.), Japanese andromeda (Pieris japonica), mock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…The technique of photoacoustics has been applied to photosynthetic systems for some time (10,26,30) with a variety of useful results, including the direct measurement of 02 formation in intact leaves (8,11,28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique of photoacoustics has been applied to photosynthetic systems for some time (10,26,30) with a variety of useful results, including the direct measurement of 02 formation in intact leaves (8,11,28 …”
Section: Introductionmentioning
confidence: 99%
“…By selection of excitation wavelength, we have determined the TE for linear electron flow through PSII to PSI and that for cyclic electron flow in PSI and possibly in PSII. The energy storage in PSII and in PSI were determined by varying flash intervals and by use of inhibitors.The technique of photoacoustics has been applied to photosynthetic systems for some time (10,26,30) with a variety of useful results, including the direct measurement of 02 formation in intact leaves (8,11,28 …”
mentioning
confidence: 99%
“…Recent studies have demonstrated that the PA 02 signal is influenced by a PSI-mediated 02 uptake process and possibly by other 02-consuming processes of the cell (9,14). If S02 has any inhibitory effect on these processes, it could cause an increase in 02 signal amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…A gas-coupled microphone in a closed chamber is used as a detector on the ms time scale. This method allows measurements of the photosynthetic thermal efficiency, or energy storage, and of the optical cross-section of the light harvesting systems (Canaani et al, 1984;Mauzerall, 1990;Braslavsky & Heibel, 1992). However, the time resolution is low, typically about 30 μs, and inappropriate for obtain thermodynamic parameters on the microsecond and nanosecond time scales.…”
Section: Enthalpy Entropy and Volume Changes Of Photosynthetic Reacmentioning
confidence: 99%
“…Measuring the energetics of photobiological reactions in vivo is of more interest because the local environment of photosystems may exert a prevailing consequence on their kinetics and thermodynamics. Pulsed photoacoustics via a microphone detector revealed the oxygen evolution and oxygen uptake in vivo on the millisecond time scale (Mauzerall, 1990). Using a piezo film detector, the in vivo enthalpy and volume changes of photosystem I and photosystem II of Synechocysits sp.…”
Section: Enthalpy Entropy and Volume Changes Of Photosynthetic Reacmentioning
confidence: 99%